Exploring the link between student placement learning in business organizations and self-employment preparatory behaviours. Issue 6 (December 2022) - Okolie, Ugochukwu Chinonso; Elom, Chinyere O.; Onajite, Godwin O.; Abonyi, Sunday Okechukwu; Igwe, Paul A.
This study draws on social cognitive career theory to test a moderated mediation model of self-employment preparatory behaviours in university students undertaking placement learning in a business organization (PLBO). Using time-lag data from 337 university students undertaking work placement in 123 business organizations, the study hypotheses were tested using PROCESS Macro 3.5. The results revealed that PLBO significantly influenced student self-employment self-efficacy, self-employment outcome expectations and self-employment preparatory behaviours. Also, self-employment self-efficacy and self-employment outcome expectations mediated the relationship between work placement learning and self-employment preparatory behaviours. However, placement supervisor support interacted with PLBO such that greater support from placement supervisors contributed to stronger self-employment preparatory behaviours. The placement learning supervisor support moderated the indirect effect of PLBO on self-employment preparatory behaviours via self-employment self-efficacy and self-employment outcome expectations at all levels (−1SD, Mean and +1SD).